The Impact of Artificial Sweeteners on Body Weight Control and Glucose Homeostasis - Pang, Michelle D.; Goossens, Gijs H.; Blaak, Ellen E. (Frontiers in Nutrition, 2021)
A poor diet is one of the leading causes for noncommunicable diseases. Due to the increasing prevalence of overweight and obesity, there is a strong focus on dietary overconsumption and energy restriction. Many strategies focus on improving energy balance to achieve successful weight loss. One of the strategies to lower energy intake is refraining from sugars and replacing them with artificial sweeteners, which maintain the palatability without ingesting calories. Nevertheless, the safety and health benefits of artificial sweeteners consumption remain a topic of debate within the scientific community and society at large. Noteworthy, artificial sweeteners are metabolized differently from each other due to their different properties. Therefore, the difference in metabolic fate of artificial sweeteners may underlie conflicting findings that have been reported related to their effects on body weight control, glucose homeostasis, as well as underlying biological mechanisms. Thus, extrapolation of the metabolic effects of a single artificial sweetener to all artificial sweeteners is not appropriate. Although many rodents studies have assessed the metabolic effects of artificial sweeteners, long-term studies in humans are scarce. The majority of clinical studies performed thus far report no significant or slight beneficial effects of artificial sweeteners on body weight and glycemic control, but it should be emphasized that the study duration of most studies was limited. Clearly, further well controlled, long-term human studies investigating the effects of different artificial sweeteners and their impact on gut microbiota, body weight regulation and glucose homeostasis, as well as the underlying mechanisms, are warranted.